Laparoscopic splenectomy both for primary cytoreductive surgery for advanced ovarian cancer and for secondary surgery for isolated spleen recurrence: feasibility and technique - Antonio Macciò; Elisabetta Sanna; Fabrizio Lavra; Giacomo Chiappe; Marco Petrillo; Clelia Madeddu (BMC Surgery, 2021)
Abstract Background This study investigated the feasibility and safety of laparoscopic splenectomy conducted in the contexts of both laparoscopic secondary surgery for isolated recurrence in the spleen and primary laparoscopic cytoreductive surgery for advanced ovarian cancer. Methods We performed a perspective observational study including all consecutive patients with ovarian cancer who underwent laparoscopic splenectomy as part of primary cytoreductive procedures for advanced stage ovarian cancer or secondary surgery for isolated splenic recurrence between January 2016 and May 2020. Results We enrolled 13 consecutive patients, candidate to laparoscopic splenectomy as part of primary cytoreductive procedures for advanced stage ovarian cancer (6 patients) or secondary surgery for isolated splenic recurrence of platinum-sensitive ovarian cancer (7 patients). Median operative time (509 min [range, 200–845]) for primary cytoreductive surgery varied according to surgical complexity depending on the extensiveness of the disease. Median operative time for secondary surgery for isolated splenic metastasis was 253 min (90–380). Only 1 patient with isolated splenic recurrence required conversion to an open approach. No intraoperative complication occurred, and no intraoperative blood transfusions were required. Median hospital stay was 3 days (range, 2–5) for isolated recurrence and 9 days (7–18) for primary cytoreductive surgery. Complete tumor resection was achieved in all patients. Median time from surgery to adjuvant chemotherapy was 16 days (7–24). All six patients who underwent laparoscopic splenectomy during primary cytoreductive surgery remain alive, four of whom exhibit no evidence of disease (median follow-up 25 months [4–36]). Among patients who underwent laparoscopic splenectomy during secondary surgery for isolated splenic relapse, all patients are alive and only one had a central diaphragmatic relapse 2 years after surgery (median follow-up 17 months ([5–48 months]). Conclusions The laparoscopic approach to splenectomy is feasible and safe both in patients undergoing primary cytoreductive surgery for advanced stage disease and those with isolated recurrence of ovarian cancer, without compromising survival and allowing early initiation of postoperative systemic chemotherapy.